A MOTHER DOES NOT WALK WITHOUT A DRINKING BOWL: AN ETHNOLINGUISTIC ANALYSIS OF SELECTED YORUBA PROVERBS WITH MOTHERHOOD LEXIS - Adeniyi, Adeniyi; Bolaji, Ezekiel; Kehinde, Taye (EBSU Journal of Social Sciences and Humanities, 2025)
This paper presents an ethnolinguistic analysis of selected Yoruba proverbs with motherhood lexis. The Yoruba people of Nigeria have a rich cultural heritage that is encapsulated in their proverbs which reflect their worldview and provide insight into their culture, social norms and values. The study which was conducted through a qualitative content analysis of selected Yoruba proverbs with motherhood lexis brought forward some metaphorical expressions and linguistic features of the proverbs and offered awareness into gender roles and societal expectations placed on mothers thereby contributing to a better understanding of their status apart from shedding lights on the values, beliefs ,family dynamics and behavioural norms associated with motherhood in Yoruba culture.